2007
DOI: 10.1016/j.nucmedbio.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of [18F]fluoroalkyl derivatives of dihydrotetrabenazine in rat and monkey brain

Abstract: The specific binding and regional brain pharmacokinetics of new fluorine-18 labeled radioligands for the vesicular monoamine transporter (VMAT2) were examined in the rat and primate brain. In the rat, 9-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…The present data confi rmed that AV-133 uptake assessed here is consistent with previous studies of the primate brain [21,25,32] . MPTP administration induced striatal dopaminergic denervation, and resulted in a decrease in VMAT2 expression (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present data confi rmed that AV-133 uptake assessed here is consistent with previous studies of the primate brain [21,25,32] . MPTP administration induced striatal dopaminergic denervation, and resulted in a decrease in VMAT2 expression (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Multi-tracer PET imaging in a monkey model of PD induced by chronic MPTP treatment at a low dose shows progressive nigrostriatal dopaminergic neurodegeneration, and this results in a reduced storage capacity of VMAT2 and decreased uptake of [19] , suggesting that VMAT2 binding sites are AV-133) is a novel 18 F-labeled tetrabenazine derivative that selectively binds to VMAT2 with high affi nity [20,21] . [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the occipital cortex appears to be a preferred reference region in human brain imaging studies apparently because the data obtained are less variable and of consistently higher values as compared with those using cerebellar cortex as the reference region (Chan et al, 1999). However, animal studies have repeatedly showed that the cerebellar cortex contains less DTBZ-binding sites than cerebral cortices (Scherman et al, 1988;Darchen et al, 1989;Vander Borght et al, 1995) and in the development of new DTBZ-based PET tracers the cerebellum, for practical reasons, continues to be used as the reference region in preclinical studies (Kilbourn et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…18 F-AV-133 displayed an excellent binding affinity (K i 5 0.11 nM, rat striatal homogenates) for VMAT2 (15,16). Successful imaging studies in rodents and monkeys using 18 F-AV-133 have been reported (17). An initial trial to assess the reduction of VMAT2 binding sites in patients with PD and dementia with Lewy bodies was performed by Koeppe et al (18) and Suzuki et al (19).…”
mentioning
confidence: 99%